The Influence of Political Ideology on Legal Decision-Making - Hermawan, Asep (Politeknik Siber Cerdika Internasional, 2025)
The intersection of political ideology and judicial decision-making has been a subject of extensive debate in legal and political scholarship. Courts, especially in common law jurisdictions, are often viewed as impartial arbiters of justice. However, empirical research suggests that judges' ideological leanings influence their rulings, particularly in politically charged cases. This study aims to explore the extent to which political ideology shapes judicial reasoning and decision-making processes. Utilizing a qualitative approach, this research analyzes judicial opinions, legal commentaries, and case law from high courts in various jurisdictions. A comparative analysis of rulings on constitutional rights, administrative law, and social justice issues is conducted to identify patterns linked to ideological stances. The findings indicate that conservative-leaning judges are more likely to favor restrictive interpretations of statutes and constitutional provisions, whereas liberal-leaning judges tend to adopt an expansive approach, particularly on civil rights and regulatory matters. Additionally, the study highlights how external political pressures and institutional structures mediate these ideological influences. The study concludes that while judicial decision-making is framed within legal principles, political ideology remains an underlying factor shaping legal interpretations. Recognizing these influences can inform judicial selection processes and foster transparency in legal reasoning. This research contributes to legal scholarship by providing a nuanced understanding of the ideological dimensions of judicial behavior, emphasizing the need for judicial accountability and impartiality in upholding the rule of law.